The lady in the Coppergate Tower - Allen, Nancy Campbell, 1969- (Proper romance., 2019)
Hazel Hughes finds romance and danger as she travels to Romania with her employer, Dr. Sam MacInnes, and her uncle, Count Petrescu, in an attempt to save her twin sister, who is slowly going mad inside the Coppergate Tower. Hazel and Sam must fight their way past vampires, clockwork beasts, and their own insecurities as they try to reach her sister in the impenetrable tower before time runs out.